Revenue Performance of Sweet Corn (Pioneers) and Hybrid Corn (Bisi-2) Farmers in Pukdale Village, East Kupang District, Kupang Regency - tanaem, cheisya; Bano, Maria; Kapioru, Charles (Talenta Publisher, 2020)
Limited land owned by farmers which in the same land farmers grow 2 types of maize with different time, namely sweet corn and hybrid corn within 1 year. In the dry season farmers grow hybrid corn and in the rainy season farmers grow sweet corn. Farmers capital for purchase production facilities, especially for the purchase of seeds, fertilizers, and medicines whose prices are getting higher and higher, in addition to the price of corn and hybrid corn which always increases fluctuations, and in terms of cost and time of hybrid corn is higher than sweet corn. This will have an impact on income obtained by farmers. Sampling in this study was carried out by proportional random sampling. Determination of a large sample for the participation of smaller than 10000 can use the Slovin formula (Soekidjo, 2003) with the formula, to answer the objective, it can be used an analysis using total corn farming with total corn farming at one planting season, and to answer the purpose of both methods used using Gross Profit Margin. The results showed that the total income of hybrid maize and sweet corn in the research location was IDR.49.425.000 with an average income per respondent of IDR.852.155 / season and the average income per hectare was IDR. 1.433.855 / season. While the total income of sweet corn farming obtained by respondent farmers is IDR.55.383.000 with an average income per respondent is IDR. 1.065.057 / season and the average income per Ha is IDR. 3.018.147 / season. The percentage of gross profit margin shows that the percentage of sweet corn of 20.63% is received within 2 months and while hybrid corn is 23.20% received within 3 months. REFERENCES Andi B. 2016. Analisis Kelayakan Usahatani Jagung Pada Lahan Kering Di Zona Agroekologi Iiiay Wilayah Timor Barat. Skripsi. Fakultas Pertanian. Universitas Nusa Cendana. Kupang. BPS Kabupaten Kupang.2018.Statistik Pertanian Kabupaten Kupang. BPS NTT.2018. Statistik Pertanian NTT. Badan Pustaka Statistik NTT. Calvin Dkk. 2016. Perbandingan Pendapatan Usahtani Jagung Manis dan Jagung Biasa Di Desa Tontalete Kecamatan Kema Kabupaten Minahasa Utara. Jurnal . Derna, H. 2007. Jagung manis. Diakses di http://Derna.com/2007/Tanaman Jagung Manis. On the 7th November 2018. Djamaludin,2003.AnalisisEkonomiUsahata Jagung diDesa Nunmafo KecamatanKupang Timur Kabupaten Kupang. Skripsi Faperta Undana. Kantor Desa Pukdale (2018). Profil Desa Pukdale: Kecamatan Kupang Timur Kabupaten Kupang Palawi, 2002. Analisis Dapatan Usahatani Jagung dan Kacang Tanah dari Program Wanita di Desa Tesabela Kecamatan Kupang Barat. Skripsi Faperta Undana. Poerwanto, R.2008. Departemen Agronomi dan Hortikultura Fakultas Pertanian- IPB. Bogor Soekartawi. 2002. Analisis Usahatani. Jakarta: Penerbit Universitas Indonesia(UI-Press). Warsana.2007. Soekartawi. 1995. Ilmu Usaha Tani.UIPress. Jakarta Sugiarto. Dkk. 2007. Ekonomi Mikro. Gramedia Pustaka. Jakarta Ilmu Manajemen Industri. Pengertian Gross Profit Margin dan Rumusnya https://ilmumanajemenindustri.com/pengertian-gross-profit-margin-marjin-laba-kotor-rumus-gpm/ accessed on 6 January 2019.